NanoXAS - The in situ combination of scanning transmission X-ray and scanning probe microscopy - Wenzel, Stephan; Fink, Rainer; Raabe, Jörg; Quitmann, Christoph; Hug, Hans J.; et al. (10th International Conference on X-Ray Microscopy, 2010)
NanoXAS is a novel x-ray microscope installed at the Swiss Light Source combining laterally resolved soft x-ray spectroscopy with scanning probe microscopy. We report on first in situ studies from thin polymer blend films and magnetic materials where topographic and spectroscopic contrast are used and show how complementary imaging modes provide new insight into many materials. In the future the scanning probe tip will be used to collect photoelectrons. By this we expect a spatial resolution in the few-nm range and unique information on surface and bulk properties of nano-materials. © 2011 American Institute of Physics.